Relation between microstructure and tribological properties of high density polyethylene hybrid composites filled with untreated glass spheres, talc and calcium carbonate - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2014)
In the present work, high density polyethylene based composites filled with glass spheres, talc and calcite particles were prepared. Fillers contents in the HDPE were 5, 10, 15, and 20 wt%. The mechanical, morphological and tribological properties of the polymer composites were investigated. Substantial improvements in the some mechanical properties were obtained by the addition of filler. For example, the results showed that the elasticity modulus of composites improved with increasing the filler content. The addition of fillers to the HDPE changed significantly the friction coefficient and wear rate of the composites. HDPE filled with a high level content of fillers showed higher wear rate than pure HDPE under dry sliding. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM).
Keywords: Mechanical properties; friction; wear; high density polyethylene; talc; glass spheres; calcite; polymer composites; WEAR BEHAVIOR